CAMPR3: a database on sequences, structures and signatures of antimicrobial peptides. Issue Volume 44:Issue D1(2016) (13th October 2015) - Waghu, Faiza Hanif; Barai, Ram Shankar; Gurung, Pratima; Idicula-Thomas, Susan
Abstract: Antimicrobial peptides (AMPs) are known to have family-specific sequence composition, which can be mined for discovery and design of AMPs. Here, we present CAMPR3 ; an update to the existing CAMP database available online at www.camp3.bicnirrh.res.in . It is a database of sequences, structures and family-specific signatures of prokaryotic and eukaryotic AMPs. Family-specific sequence signatures comprising of patterns and Hidden Markov Models were generated for 45 AMP families by analysing 1386 experimentally studied AMPs. These were further used to retrieve AMPs from online sequence databases. More than 4000 AMPs could be identified using these signatures. AMP family signatures provided in CAMPR3 can thus be used to accelerate and expand the discovery of AMPs. CAMPR3 presently holds 10247 sequences, 757 structures and 114 family-specific signatures of AMPs. Users can avail the sequence optimization algorithm for rational design of AMPs. The database integrated with tools for AMP sequence and structure analysis will be a valuable resource for family-based studies on AMPs.